An Overview of Big Data Analytics in Higher Education Sector - Mai , Anh Thơ (Journal of Technical Education Science, 2018)
It has recently been an urgency to create specific solution for quality assurance in terms of education. Big data analytics came out as an efficient tool to enhance the quality of higher education. This article aims to present an overview of big data in the context of higher education, especially in Vietnam as an emerging interdisciplinary research field. The article then identifies the types of data that need to be collected, stored and analyzed at educational institutions, summarize data analytic methods that are currently being applied. Current situation of Vietnam higher education is also addressed as a background of some initial suggestions for applying big data analytics in this sector.